Bilingual Intercultural Education in Chile: The Challenge of a Traditional Educator - Vidal, Tatiana Aguayo (2022)
The acknowledgement of indigenous people within the politics of intercultural education continues to be rooted in a functional and assimilationist approach, in which intercultural education is developed without touching the structures of power-knowledge, generating a hegemony of school learning. In this context, an ethnographic research is carried out, which was carried out in a school located in the commune of Alto Biobío, in Chile. Individual and group interviews, participant observation, audio and image records were used, with the aim to understand the experience of a traditional educator in an educational establishment, within the framework of the Intercultural Bilingual Education Program. The educator's accounts were analyzed from the phenomenological perspective of inhabiting, identifying those categories that show how she promotes the recognition and self-creation of her own, that is, of the Pehuenche. Among the findings, it is established that the main processes that the educator mobilizes to inhabit the school are translation-articulation. However, these processes are not exempt from the epistemological challenges originating from the school structure. It is concluded that intercultural education depends on the pedagogical practice of going to the community's own places, trying to rescue the meaning that the community has given to the various experiences. Among the recommendations, it is suggested to consider in the pedagogical reflections the translation and articulation processes that make up the practices proposed by the traditional educator, in addition to making these processes explicit and problematizing, since they are not only important in intercultural education initiatives, but in all practices pedagogical that tries to be appropriate and culturally sustainable.